Pharmacist-assisted electronic prescribing at the time of admission to an inpatient orthopaedic unit and its impact on medication errors: a pre- and postintervention study. (July 2019) - Tran, Tim; Taylor, Simone E.; Hardidge, Andrew; Mitri, Elise; Aminian, Parnaz; George, Johnson; Elliott, Rohan A.
Background: Prescribing and administration errors related to pre-admission medications are common amongst orthopaedic inpatients. Postprescribing medication reconciliation by clinical pharmacists after hospital admission prevents some but not all errors from reaching the patient. Involving pharmacists at the prescribing stage may more effectively prevent errors. The aim of the study was to evaluate the effect of pharmacist-assisted electronic prescribing at the time of hospital admission on medication errors in orthopaedic inpatients. Methods: A pre- and postintervention study was conducted in the orthopaedic unit of a major metropolitan Australian hospital. During the 10-week intervention phase, a project pharmacist used electronic prescribing to assist with prescribing admission medications and postoperative venous thromboembolism (VTE) prophylaxis, in consultation with orthopaedic medical officers. The primary endpoint was the number of medication errors per patient within 72 h of admission. Secondary endpoints included the number and consequence of adverse events (AEs) associated with admission medication errors and the time delay in administering VTE prophylaxis after elective surgery (number of hours after recommended postoperative dose-time). Results: A total of 198 and 210 patients, pre- and postintervention, were evaluated, respectively. The median number of admission medication errors per patient declined from six pre-intervention to one postintervention ( p < 0.01). A total of 17 AEs were related to admission medication errors during the pre-intervention period compared with 1 postintervention. There were 54 and 63 elective surgery patients pre- and postintervention, respectively. The median delay in administering VTE prophylaxis for these patients declined from 9 h pre-intervention to 2 h postintervention ( p < 0.01). Conclusions: Pharmacist-assisted electronic prescribing reduced the number of admission medication errors and associated AEs.